Bulk carbon isotope excursions of the Cenomanian through Turonian of mid-Cretaceous in southern Tibet - Li, X; Wang, C; Jenkyns, H; Cheng, X; Cui, J; Hu, X (2005)
In the past, huge high-resolution data of carbon and oxygen isotopic values on paleoceanography of the Cenomanian-Turonian and on anoxic event of its boundary passage were derived from DSDP, ODP and deeper basins in Euramerica, but few and rough data relevant came from southern Tibet, China. The new carbon isotope high-resolution data of the Cenomanian-Turonian in this paper aim to provide a correlation among Euramerica, DSDP, ODP and southeastern Tethys Ocean (southern Tibet), and try to characterize the carbon isotopic curve in shallower lithofacies background. Carbon isotopic values obtained from the Gongzha Section of Tingri and the Zongshan Section of Gamba, in southern Tibet, indicate a long-term tendency of Cenomanian through Turonian similar to those from Tethys even globe. The carbon isotopic values seldom change in the middle-late Cenomanian. An abrupt and high-amplitude positive excursion occurs near the passage bed of Cenomanian and Turonian, then goes negative in gradual in whole Turonian. At the same time, two negative excursion troughs are recognized at both the middle H. helvetica zone and the boundary of the H. helvetica and M. sigali zones by a moderate positive area between, which is the same as in Europe and ODP in time and pace and is in harmony with the global carbon cycle and climate changes. However, the much alterable excursions and paces of the δ13C value at Gamba are different from those at Tingri and other locations in the world. The former difference may be the result of diagenetic overprint, and the latter may be mistaken biozone positions. According to the potential correlation tool of carbon isotopes, it is suggested that the horizon of the Cenomanian-Turonian boundary may need to be promoted upward ca. 40 m. Lack of typical organic black shale at the Cenomanian-Turonian boundary in shallow sea area including southern and northern Tibetan Tethys Himalayas indicates the high δ13C values in the oceanic sediments are not the unique result of the oceanic anoxic event but a mixed response of global carbon reservoir.